Molecular principles underlying dual RNA specificity in the Drosophila SNF protein - Gert Weber (Nature Portfolio, 2018)
It remains poorly understood how a single RNA-binding protein recognizes diverse RNA targets. Here the authors use an integrative approach to study the binding of spliceosomal SNF protein to U1 and U2 small nuclear RNAs in the presence or absence of auxiliary protein U2A’ and show how SNF’s conformational dynamics are tuned to recognize different stem-loop structures.